Inflammation in Cardiovascular Tissue Engineering: The Challenge to a Promise: A Minireview - Agneta Simionescu; Jason B. Schulte; George Fercana; Dan T. Simionescu (International Journal of Inflammation)
Tissue engineering employs scaffolds, cells, and stimuli brought together in such a way as to mimic the functional architecture of the target tissue or organ. Exhilarating advances in tissue engineering and regenerative medicine allow us to envision in vitro creation or in vivo regeneration of cardiovascular tissues. Such accomplishments have the potential to revolutionize medicine and greatly improve our standard of life. However, enthusiasm has been hampered in recent years because of abnormal reactions at the implant-host interface, including cell proliferation, fibrosis, calcification and degeneration, as compared to the highly desired healing and remodeling. Animal and clinical studies have highlighted uncontrolled chronic inflammation as the main cause of these processes. In this minireview, we present three case studies highlighting the importance of inflammation in tissue engineering heart valves, vascular grafts, and myocardium and propose to focus on the endothelial barrier, the “final frontier” endowed with the natural potential and ability to regulate inflammatory signals.